Taking stock of research on hybrid organizations: Enriching theoretical perspectives, extending empirical contexts, and expanding practical relevance - Ratinho, Tiago; Bruneel, Johan (Journal of business research, 2024)
Organizations are increasingly subject to conflicting demands arising from shifting consumer desires, evolving regulatory backgrounds, and emergent sociocultural trends. The concept of the hybrid organization (HO) has rapidly emerged as a powerful tool to explain organizations’ deployment of multiple logics to respond effectively to these external demands. However, despite its popularity, the theoretical concept and, crucially, its practical implications remain unclear. By combining state-of-the-art bibliometric techniques with content analysis, we delineate the current body of literature on HOs, uncover its patterns, reveal its intellectual underpinnings, and suggest avenues for future research. Our database of 596 academic works published between 1987 and 2019 reveals that contemporary debate surrounding HOs is structured around 11 major themes and anchored in four dominant theoretical foundations. We conclude by offering guidance on ways to enrich theoretical perspectives, extend empirical contexts, and expand the practical relevance of the body of knowledge on HOs.